The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1007/bf00255910
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone metabolism in the isolated perfused rat liver

Abstract: The hepatobiliary pharmacokinetics of mitoxantrone, a new anthracenedione derivative, was studied in the isolated perfused rat liver. Mitoxantrone was administered in doses of 0.2 and 0.4 mg/kg body weight. Multiple bile samples were obtained for 4 hours. Mitoxantrone and three metabolites were separated by high-performance thin-layer chromatography (HPTLC) and measured at 610 nm. Following 0.2 mg mitoxantrone/kg body wt, 25.8% +/- 2.6% of the administered dose was excreted in the bile during 4 h, the major me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…These results are in close agreement with those previously reported. The observation in man that 28% of the dose is excreted in the feces (8) within five days as well as the high rate of biliary excretion in the rat (13,22), supports the concept that bile may be the major route for the elimination of mitoxantrone. Future studies should address the biliary elimination of mitoxantrone in patients with normal and impaired liver function and assess the metabolic capabilities under these conditions as well as the amount of mitoxantrone metabolites excreted in the bile.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These results are in close agreement with those previously reported. The observation in man that 28% of the dose is excreted in the feces (8) within five days as well as the high rate of biliary excretion in the rat (13,22), supports the concept that bile may be the major route for the elimination of mitoxantrone. Future studies should address the biliary elimination of mitoxantrone in patients with normal and impaired liver function and assess the metabolic capabilities under these conditions as well as the amount of mitoxantrone metabolites excreted in the bile.…”
Section: Discussionmentioning
confidence: 65%
“…Reported pharmacokinetic data are controversial, with the elimination half-life varying between 56 minutes and 42.6 hours (8)(9)(10)(11)(12). Our group has prcviously reportcd on the extensive metabolism in the isolated perfused rat liver (13,14) and has described metabolites in man (15).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Thirdly, urine HPLC chromatograms revealed up to three polar metabolites, which appeared identical to those previously observed in rat bile (27). Finally, Ehninger et al (28) have shown recently, using an isolated perfused rat liver model and thin layer chromatography assay techniques, that mitoxantrone is actively metabolised with up to three more polar compounds appearing on the thin layer plates.…”
Section: Mitoxantrone Pharmacokinetics Following Intravenous Administmentioning
confidence: 99%
“…The biliary excretion of mitoxantrone in rats has not been fully investigated. The percentage of the dose of mitoxantrone excreted in bile has been reported in one published article and two abstracts 16–18. In one study using isolated perfused rat livers, 25.8 ± 2.6% of a 0.2 mg/kg dose was excreted into bile during 4 h, with the parent drug accounting for about 5.5%.…”
Section: Introductionmentioning
confidence: 99%